2021
DOI: 10.1037/xge0000933
|View full text |Cite
|
Sign up to set email alerts
|

Engaging proactive control: Influences of diverse language experiences using insights from machine learning.

Abstract: We used insights from machine learning to address an important but contentious question: is bilingual language experience associated with executive control abilities? Specifically, we assess proactive executive control for over 400 young adult bilinguals via reaction time on an AX continuous performance task (AX-CPT). We measured bilingual experience as a continuous, multidimensional spectrum (i.e., age of acquisition, language entropy, and sheer second language exposure). Linear mixed effects regression analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 107 publications
(207 reference statements)
2
60
0
Order By: Relevance
“…The most critical criterion for distinguishing SLC from DLC was the mean number of languages used across seven contexts. Unlike the entropy measures used by Gullifer and Titone [ 41 , 42 ] and by Kalamala et al [ 19 ] participants were not asked to make fine-grain judgments about the percentage of time using each language in each context. Because our data was collected before becoming aware of the entropy measures, we had doubted (and remain skeptical) that bilinguals could accurately judge these percentages and maintain the motivation to do so across seven contexts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most critical criterion for distinguishing SLC from DLC was the mean number of languages used across seven contexts. Unlike the entropy measures used by Gullifer and Titone [ 41 , 42 ] and by Kalamala et al [ 19 ] participants were not asked to make fine-grain judgments about the percentage of time using each language in each context. Because our data was collected before becoming aware of the entropy measures, we had doubted (and remain skeptical) that bilinguals could accurately judge these percentages and maintain the motivation to do so across seven contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the insight and care that has been applied to theorizing and measuring different aspects of bilingual language control, future research must improve on this foundation. At this time, it is impossible to determine if the sporadic support of the ACH is genuine or the product of an idiosyncratic combination of bilinguals and EF tests that resonates with tendencies toward confirmation bias [ 31 ] and overfitting of the data [ 42 ]. Finally, it is important to acknowledge that the value and scope of the ACH in guiding research and understanding of bilingual language control go far beyond the predictions that it inspired about bilingual advantages in EF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical group comparison would categorize these two experiences as "bilingual", but it is plausible that Maryam's consistent recruitment of multiple languages has cultivated greater attention to environmental social cues in predicting the linguistic preferences of her conversational partners, which over time may exercise her mentalizing capacity. To mitigate the erasure of these and other important individual differences, more and more studies are relying on the continuous, rather than categorical, assessment of bilingual language experiences (discussed in Gullifer & Titone, 2020).…”
Section: Mentalizing and Bilingualismmentioning
confidence: 99%
“…Thus, language entropy can quantify the degree of bilingualism, in terms of people's experiences navigating dual-language social environments. Gullifer and Titone (2020) found that greater environmental linguistic diversity, as measured through entropy, predicts stronger proactive executive control in particular, suggesting that this index relates to attendance of contextual information, including social context. Similarly, Fan, Liberman, Keysar, and Kinzler (2015) identified that diverse sociolinguistic environments enhance mentalizing capacities, even among monolinguals, implicating the social consequences of bilingualism on flexible social cognition (the SOCIAL-PRAGMATIC ACCOUNT of bilingual social cognition; see also Tiv et al, 2019bTiv et al, , 2020.…”
mentioning
confidence: 97%